Morphological Changes in Cortical and Subcortical Structures in Multiple System Atrophy Patients With Mild Cognitive Impairment - Cao, Chenghao; Wang, Qi; Yu, Hongmei; Yang, Huaguang; Li, Yingmei; Guo, Miaoran; Huo, Huaibi; Fan, Guoguang (Frontiers in Human Neuroscience, 2021)
Objective: This study aimed to investigate the morphometric alterations in the cortical and subcortical structures in multiple system atrophy (MSA) patients with mild cognitive impairment (MCI), and to explore the association with cognitive deficits. Methods: A total of 45 MSA patients (25 MSA-only, 20 MSA-MCI) and 29 healthy controls were recruited. FreeSurfer software was used to analyse cortical thickness, and voxel-based morphometry was used to analyse the grey matter volumes. Cortical thickness and grey matter volume changes were correlated with cognitive scores. Results: Compared to healthy controls, both MSA subgroups exhibited widespread morphology alterations of brain structures in the fronto-temporal regions. Direct comparison of MSA-MCI and MSA-only patients showed volume reduction in the left superior and middle temporal gyrus, while cortical thinning was found in the left middle and inferior temporal gyrus in MSA-MCI patients. Cortical thinning in the left middle temporal gyrus correlated with cognitive assessment and disease duration. Conclusions: Structural changes in the brain occur in MSA-MCI patients. The alteration of brain structure in the left temporal regions might be a biomarker of cognitive decline in MSA-MCI patients.